Psychological Safety and Communication Difficulties of Teachers and Students During Long-term Online Training - P. A. Kislyakov; E. A. Shmeleva; I.-L. S. Meerson (Высшее образование в России, 2023)
Due to the growing concerns related to the psychological well-being of students and teachers during a long and intensive online training, it becomes necessary for teachers, psychologists, practitioners to take measures to prevent threats to online communication and identify personal resources of psychological security in the online environment.The purpose of the study was to identify the communicative difficulties of long-term online learning during the COVID-19 pandemic, and the personal resources of students and teachers that contribute to ensuring their psychological safety.The study was conducted in February-March 2022. The study sample included 132 students and 40 teachers of the Faculty of Psychology of the Russian State Social University (Moscow). The following techniques were used: “The test of hardiness” (S. Muddy, in the Russian-language adaptation of E.N. Osin, E.I. Rasskazova), “The scale of subjective well-being” (A. Perrudet-Badoux, G.A. Mendelssohn, J. Chiche, in the Russian-language adaptation of M.V. Sokolova), “Methodology for assessing the level of sociability” (V.F. Ryakhovsky), questionnaires “Difficulties of online communication” for students and teachers. The empirical data obtained were interpreted and processed using qualitative and quantitative methods of analysis, including: descriptive statistics, frequency analysis, Spearman correlation analysis. The study showed that during the long-term distance learning, students and teachers experienced significant difficulties in online educational communication, had low levels of subjective well-being, resilience and sociability. These personal qualities are systemic in nature, interrelated and can act as resources to ensure the psychological safety of subjects of education, prevention or coping with difficulties of online communication and hybrid forms of learning.The data obtained make it necessary for teachers to create psychodidactic conditions for a safe online educational environment in which students will be involved as subjects of education, will be able to freely share their opinions and not be afraid to make a mistake, will feel belonging to a group and protected from verbal aggression.